D2‐40‐positive lymphatic vessel invasion is not a poor prognostic factor in stage I lung adenocarcinoma. (20th May 2013) - Shimizu, Kei; Funai, Kazuhito; Sugimura, Haruhiko; Sekihara, Keigo; Kawase, Akikazu; Shiiya, Norihiko
<x xml:space="preserve">Abstract</x> The present study investigates whether lymphatic vessel invasion (LVI) detected by D2‐40 staining is a prognostic factor for stage I adenocarcinoma of the lung. We retrospectively reviewed 124 patients who underwent complete resection for stage I adenocarcinoma of the lung from January 1983 to June 2003. LVI was microscopically evaluated using D2‐40 immunostaining. The median follow‐up was 71 months. The LVI positive rate was 37%. The 5‐year cancer‐specific survival rates of the D2‐40 positive LVI and negative groups were 88.8% and 84.3%, respectively (P = 0.630). The stage I lung adenocarcinoma patients who were determined to be LVI positive based on D2‐40 immunostaining did not have a significantly poorer prognosis than the LVI negative cases. Thus, lymphatic microinvasion may not be a prognostic indicator in early lung cancer, although advanced LVI does appear to correlate with survival. It is therefore unnecessary to use D2‐40 immunostaining to diagnose LVI in practical settings, and Hematoxylin‐Eosin and Elastica van Gieson staining should continue to be used to predict the prognosis of patients with stage I lung adenocarcinoma.